1983
DOI: 10.1073/pnas.80.15.4644
|View full text |Cite
|
Sign up to set email alerts
|

ts A1S9 locus in mouse L cells may encode a novobiocin binding protein that is required for DNA topoisomerase II activity.

Abstract: Nuclear novobiocin binding proteins (NBPs) from a set of mouse L cells have been extensively purified by affinity chromatography on novobiocin-Sepharose columns. The NBPs, specifically eluted with 100 ,ug of novobiocin per ml, exhibited equivalent DNA topoisomerase activities (measured as ATP-dependent relaxation or catenation of #X174 replicative-form I DNA substrate) when extracted from equal numbers of wild-type (WT-4) mouse L cells growing logarithmically at 34WC or at 38.50C, from ts A1S9 cells similarly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…I was particularly impressed by an earlier publication from that group showing that it was possible to isolate temperature-sensitive mutants in mouse L-cells [1]. Although the nature of the defect was not known at the time, it was eventually localized to a protein involved in DNA topoisomerase II activity [2]. By the time I arrived, it had pretty much been decided that the Chinese hamster ovary (CHO) cells were the cell line of choice.…”
Section: The Cellular Physiology and Biochemistry Of Multidrugmentioning
confidence: 99%
“…I was particularly impressed by an earlier publication from that group showing that it was possible to isolate temperature-sensitive mutants in mouse L-cells [1]. Although the nature of the defect was not known at the time, it was eventually localized to a protein involved in DNA topoisomerase II activity [2]. By the time I arrived, it had pretty much been decided that the Chinese hamster ovary (CHO) cells were the cell line of choice.…”
Section: The Cellular Physiology and Biochemistry Of Multidrugmentioning
confidence: 99%
“…Biochemical and biological studies have revealed that the ts A1S9 and is Cl genetic loci, respectively, encode a DNA topoisomerase II activity [26] and a DN A-chain-elongation factor [Gam and Sheinin, unpub lished], which can be distinguished from the already known DNA polymerase-« and -[1 [27]. Both gene products are required for semiconservative DNA replication, which occurs normally during the DNA-synthetic, or S, phase of the cell duplication cycle [3,5,11,12,24], Because they arrest at unique stages early in S phase, they are designated DNA'7S'\ The is 2 mouse fibroblast arrests at the Gi/S interface [28] upon temperature inactivation of a polypeptide which acts to effect S-phase entry, perhaps by facilitating interaction of DNA polymerase-a and DNA primase [27].…”
mentioning
confidence: 99%
“…This is supported by the fact that the concentrations of antibiotics which interfere with EA synthesis are fairly consistent with those required for inhibition of topoisomerase activity, in vitro [20][21][22].…”
Section: Discussionmentioning
confidence: 56%